An examination of protist diversity in serpentinization-hosted ecosystems of the Samail Ophiolite of Oman - Howells, Alta E. G.; De Martini, Francesca; Gile, Gillian H.; Shock, Everett L. (Frontiers in Microbiology, 2023)
In the Samail Ophiolite of Oman, the geological process of serpentinization produces reduced, hydrogen rich, hyperalkaline (pH > 11) fluids. These fluids are generated through water reacting with ultramafic rock from the upper mantle in the subsurface. On Earth’s continents, serpentinized fluids can be expressed at the surface where they can mix with circumneutral surface water and subsequently generate a pH gradient (~pH 8 to pH > 11) in addition to variations in other chemical parameters such as dissolved CO2, O2 and H2. Globally, archaeal and bacterial community diversity has been shown to reflect geochemical gradients established by the process of serpentinization. It is unknown if the same is true for microorganisms of the domain Eukarya (eukaryotes). In this study, using 18S rRNA gene amplicon sequencing, we explore the diversity of microbial eukaryotes called protists in sediments of serpentinized fluids in Oman. We demonstrate that protist community composition and diversity correlate significantly with variations in pH, with protist richness being significantly lower in sediments of hyperalkaline fluids. In addition to pH, the availability of CO2 to phototrophic protists, the composition of potential food sources (prokaryotes) for heterotrophic protists and the concentration of O2 for anaerobic protists are factors that likely shape overall protist community composition and diversity along the geochemical gradient. The taxonomy of the protist 18S rRNA gene sequences indicates the presence of protists that are involved in carbon cycling in serpentinized fluids of Oman. Therefore, as we evaluate the applicability of serpentinization for carbon sequestration, the presence and diversity of protists should be considered.